Pelaksanaan Pembelajaran Sosiologi di Rumah pada Masa Pandemi COVID-19 di SMA Swasta Sudirman Kupang - Fabianus Lere (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The purpose of this qualitative study was to determine the implementation of sociology learning at home during the COVID-19 pandemic at Sudirman Private High School Kupang and its inhibiting factors. The data of the study were obtained from the principal, parents, students and teachers, through structured interviews, observation, and documentation. The data were analyzed through data reduction, data display, and conclusions. The study showed that first, the implementation of learning at home or online was quite well, using Zoom, Google Classroom, and WhatsApp, depending on the internet network where the learning takes place. Second, the inhibiting factors found were the students do not have cellphones and laptops, and the limited internet quota.